Hypoxia-inducible protein 2 is a novel lipid droplet protein and a specific target gene of hypoxia-inducible factor-1 - Gimm, Tina; Wiese, Melanie; Teschemacher, Barbara; Deggerich, Anke; Schödel, Johannes; Knaup, Karl; Hackenbeck, Thomas; Hellerbrand, Claus; Amann, Kerstin Ute; Wiesener, Michael; Höning, Stefan; Eckardt, Kai-Uwe; et al. (The FASEB Journal, 2010)
Hypoxia-inducible protein 2 (HIG2) has been implicated in canonical Wnt signaling, both as target and activator. The potential link between hypoxia and an oncogenic signaling pathway might play a pivotal role in renal clear-cell carcinoma characterized by constitutive activation of hypoxia-inducible factors (HIFs), and hence prompted us to analyze HIG2 regulation and function in detail. HIG2 was up-regulated by hypoxia and HIF inducers in all cell types and mouse organs investigated and abundantly expressed in renal clear-cell carcinomas. Promoter analyses, gel shifts, and siRNA studies revealed that HIG2 is a direct and specific target of HIF-1, but not responsive to HIF-2. Surprisingly, HIG2 was not secreted, and HIG2 overexpression neither stimulated proliferation nor activated Wnt signaling. Instead, we show that HIG2 decorates the hemimembrane of lipid droplets, whose number and size increase on hypoxic inhibition of fatty acid β-oxidation, and colocalizes with the lipid droplet proteins adipophilin and TIP47. Normoxic overexpression of HIG2 was sufficient to increase neutral lipid deposition in HeLa cells and stimulated cytokine expression. HIG2 could be detected in atherosclerotic arteries and fatty liver disease, suggesting that this ubiquitously inducible HIF-1 target gene may play an important functional role in diseases associated with pathological lipid accumulation. © FASEB.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Gene expression; Lipid metabolism; Promoter; Renal clear-cell carcinoma